Web-powered databases - Taniar, David; Rahayu, Johanna Wenny (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2003)
This book provides a snapshot of current research and development activities in the area of Web or Internet databases. Its content supplies potential answers to many questions that have been raised regarding database accesses through the Web. The book also provides a number of case studies of successful Web database applications, including multiple-choice assessment through the Web, an online pay claim, a product catalogue, and content management and dynamic Web pages
Includes bibliographical references. - Title from ebook home page (viewed on July 25, 2010)
Keywords: Web databases